2021
DOI: 10.1002/anie.202109068
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐II Hydrogen‐Bonded Organic Frameworks (HOFs) Used for Target‐Specific Amyloid‐β Photooxygenation in an Alzheimer's Disease Model

Abstract: Phototherapyh as emerged as ap owerful approach for interrupting b-amyloid (Ab)s elf-assembly.H owever, deeper tissue penetration and safer photosensitizers are urgent to be exploited for avoiding damaging nearby normal tissues and improving therapeutic effectiveness.Ahydrogen-bonded organic framework (HOF)-based NIR-II photooxygenation catalyst is presented here to settle the abovementioned challenges.B ye ncapsulating the pyridinium hemicyanine dye DSM with alarge two-photon absorption (TPA) cross-section

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 103 publications
0
51
0
Order By: Relevance
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Light-responsive nanomaterials are widely used in various biological fields, including antibacterial applications, cancer therapy, and bioimaging under the conditions of exogenous triggering. In particular, photomediated therapeutics have recently been applied to inhibit and destroy amyloid aggregation. According to a previous report, reactive oxygen species (ROS) can induce oxidation of the Met, His, and Tyr residues of the Aβ peptide, effectively preventing Aβ aggregation and reducing Aβ-induced cytotoxicity . For example, white light-emitting diode (LED) light-responsive carbon dots (CDs) were used to suppress amyloid aggregation, break the β-sheet structure of amyloid, and disintegrate preformed Aβ aggregates by generating ROS; the inhibition and disaggregation abilities of white LED light-responsive CDs are low for Aβ due to a low 1 O 2 generation efficiency and the poor penetration depth of the LED .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, hydrogen-bonded organic frameworks (HOFs) have received increasing attention due to their potential applications in gas adsorption and separation, catalysis and photocatalysis, display and sensing, proton conduction and energy storage, as well as drug load and delivery. Different from other organic-synthon-containing crystalline porous materials such as metal-organic frameworks (MOFs) and covalent organic frameworks (COFs), which are assembled through coordination and covalent bonds, respectively, HOFs are built from hydrogen bond-dominated self-assembly. As a result, HOFs not only possess the features of explicit structures and large surface areas and favor substance diffusion and transformation, but also hold the advantages of easy access to crystalline phase as well as high structural diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to employ, for example, C 3 N 4 moieties for efficient photocatalysis, naphthalene diimide units for redox chromism, tetraphenyl ethylene skeletons for high-quantum-yield luminescence, and carbazole groups for room temperature phosphorescence. , As well-known photosensitizers, porphyrin and its derivatives are competent for energy transfer and photosensitized 1 O 2 production. This, together with the rigidity of porphyrin rings, makes them regular participants in the construction of photoactive HOFs. ,, However, few investigations have been made so far on factors that influence the photoactivity of porphyrin-based HOFs. It has been proved that Förster resonance energy transfer (FRET) between photosensitive guests and HOFs can trigger broadening of light absorption, and the photocatalytic activities of the whole materials can be simply adjusted by the numbers of guest molecules .…”
Section: Introductionmentioning
confidence: 99%